TRANSFORMASI PENGASUHAN ANAK DI ERA DISRUPSI PERSPEKTIF PSIKOLOGI KELUARGA DAN MAQASID SYARIAH - MASTAROKHAH, FUZLYI (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The transformation of child rearing in the era of disruption requires Muslim families to face new challenges related to the development of digital technology. This study aims to analyze the dynamics of child rearing through an integrative approach between family psychology and maqasid syariah. Using library research methods, this article examines various recent research results (2018–2025) on digital parenting, children's mental health, and the normative framework of Islam in parenting. The results of the study show that the use of digital technology in children brings educational opportunities, but also serious risks such as gadget addiction, cyberbullying, and moral degradation. From the perspective of maqasid syariah, digital parenting is in line with the objectives of protecting religion (hifz al-din), life (hifz al-nafs), reason (hifz al-'aql), and offspring (hifz al-nasl). The integration of these two perspectives results in an adaptive, resilient, and spiritually valuable Islamic parenting model. This article recommends the development of Islamic digital parenting guidelines, the improvement of parents' digital literacy, and multi-sector collaboration to strengthen the family's role as a bastion of character for the younger generation.